2013
DOI: 10.1038/ncomms2797
|View full text |Cite
|
Sign up to set email alerts
|

A universal description of ultraslow glass dynamics

Abstract: The dynamics of glass is of importance in materials science but its nature has not yet been fully understood. Here we report that a verification of the temperature dependencies of the primary relaxation time or viscosity in the ultraslowing/ultraviscous domain of glass-forming systems can be carried out via the analysis of the inverse of the Dyre–Olsen temperature index. The subsequent analysis of experimental data indicates the possibility of the self-consistent description of glass-forming low-molecular-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(125 citation statements)
references
References 54 publications
3
122
0
Order By: Relevance
“…It is an obvious, but controversially debated approach to trace these deviations back to a temperature-dependent apparent activation energy, strongly increasing towards low temperatures (Fig. 2(b) with inset) [1,3,4,5,47,48]. Such a behaviour may arise from an increase in cooperativity of molecular motions when the glass transition is approached [1,3,49,50].…”
Section: Glassy Dynamics As Revealed By Linear Dielectric Spectroscopymentioning
confidence: 99%
“…It is an obvious, but controversially debated approach to trace these deviations back to a temperature-dependent apparent activation energy, strongly increasing towards low temperatures (Fig. 2(b) with inset) [1,3,4,5,47,48]. Such a behaviour may arise from an increase in cooperativity of molecular motions when the glass transition is approached [1,3,49,50].…”
Section: Glassy Dynamics As Revealed By Linear Dielectric Spectroscopymentioning
confidence: 99%
“…The behavior of χ is related to the viscosity change and Qiao's work shows that the quality of the fitting depends on an appropriate description of the viscosity behavior. However, due to the many orders of magnitude change within a relatively narrow temperature region, the description of viscosity behavior is still an open problem [4,107,108]. Wang [109] showed that the DMA behavior can be fitted in the whole temperature range by coupling two KWW equations in Fourier transforms.…”
Section: Modeling Of the Mechanical Relaxation Spectrummentioning
confidence: 99%
“…The new “model free” approach, explores the reciprocal of the Dyre-Olsen (DO) activation energy temperature index 1/ I DO = [− d lnΔ E a / d ln T ] −1 , where Δ E a ( T ) defines the temperature-dependent apparent activation energy23. A preference for parameterization with the finite-temperature divergence is clearly shown and the novel metric characterizing arbitrary glass former is proposed2324.…”
mentioning
confidence: 99%